4CPS-239 Evaluation of clinical pharmacist interventions in surgical patients. (2nd March 2018) - Ngige, G; Carton, E; Zaborowski, A; Brown, A; Conyard, E; Gaskin, J
Abstract : Background: Surgical patients are at risk of medication-related adverse events, causing morbidity and mortality. Some of these surgical patients may have other medical conditions and thus are on medications prior to surgery. Published research has suggested that clinical pharmacist input on ward rounds and drug reconciliation at admission and discharge, can reduce the frequency of adverse drug events (ADEs) and medication errors. This ultimately improves the quality of patient care by reducing length of stay on admission and mortality. Purpose: To determine the effect of clinical pharmacist (CP) service on medication safety in surgical patients by: Evaluating the types and frequency of CP interventions. Determining the number of interventions that prevented a potential or actual ADE. Assessing prescribers' adherence to local guidelines. Material and methods: The study took place in two surgical wards in the hospital from January to February 2017. The CP recorded all interventions. The drug-related problems (DRPs) were classified using the Pharmaceutical Care Network Europe Classification Scheme for Drug-Related Problems V 7.0 and their potential for causing harm were rated using the National Coordinating Council for Medication Error Reporting and Prevention Index. Prescribers' adherence to local guidelines was assessed using the following: Glucose-potassium-insulin (GKI) infusion guideline for diabetics. Perioperative prescribing. Venous thromboembolism (VTE). Antimicrobials. Results: A total of 71 patients out of 122 surgical in-patients reviewed by the CP required at least one intervention. A total of 152 interventions were completed on 71 patients, with a prescriber acceptance rate of 75%. The DRP with the highest frequency was the omission of regular medication on admission or discharge (24.3%). Two-thirds of the CP interventions (68%) prevented a potential ADE and 3% prevented an actual ADE. The diabetic GKI and perioperative prescribing were complied with 100%. The CP undertook interventions on 11% and 18% of the VTE and antimicrobial prescribing, respectively. Conclusion: There was a high level of medication-related intervention in this study, which if left undetected could have led to harm. The clinical pharmacists' identification and prevention of potential and actual ADEs, as well as support for prescribers' adherence to local guidelines demonstrated a positive impact on patient safety. References and/or Acknowledgements: References and all contributors are acknowledged. No conflict of interest